Airway management for tracheal resection proximal to carina in a cat. Issue 3 (10th August 2019) - Calice, Ivana; Rocchi, Attilio
Abstract : Tracheal tumours in cats are rare, and most primary tumours respond well to complete surgical excision. Providing secure airway management during resection of the trachea is particularly challenging and in some cases represents a limitation to surgery. We present the case of a cat with a primary tracheal neoplasm located close to the carina, undergoing complete resection. Successful management of the airway was accomplished by intubating the distal tracheal stump with a modified polyvinyl chloride endotracheal tube. Effective seal of the airway and adequate ventilation of both lungs were achieved. We describe a reliable, simple, low‐cost technique which provides control of the airways even in situations where the distal stump of the trachea is either too short or non‐existent.